Weak Democracies, Failed Policies, and the Demise of Ecosystems in Poor and Developing Nations. (March 2019) - Mayer Pelicice, Fernando
The expansion of modern societies disrupted the structure and function of most ecosystems. This trend is alarming because the persistence of human activities (e.g., economy) depends on biodiversity and ecosystem services. A central question is whether modern nations will respond appropriately to protect, restore, and maintain ecosystems. In particular, it is uncertain if underdeveloped and developing (UD-D) countries have sufficient political direction to make good decisions, since they are weak or consolidating democracies, where bad political behavior is common. These countries face persistent socioeconomic problems (e.g., poverty, opportunity, basic services), and environmental issues have no priority. However, many of these nations are located in tropical latitudes, so they are hyperdiverse and provide ecosystem services with global relevance. In this opinion article, I present a brief analysis of the context (political, social, and environmental) shared by UD-D countries, to investigate how these nations have responded to the need of socioeconomic development and the ongoing loss of natural capital. I put some emphasis on my country, Brazil, to exemplify a context dominated by weak governance, socioeconomic problems, high biodiversity, and the loss of ecosystems. I argue that authorities and political systems in UD-D nations are vulnerable to weak governance and wrong decisions; bad political behavior leads to failed policies, and the persistence of social problems leads to the destruction of ecosystems. Social progress and sustainability will require political commitment, financial resources, long-term planning, and correct policies—something that UD-D countries may not achieve on their own.